University, university reform and pluriversity in Peru - Ortiz Fernández, Carolina (2018)
Understanding that knowledge is power, in the present work I explore, from a sociohistorical and gender perspective, how knowledge has been organized in San Marcos University’s structure with an emphasis on social sciences. Likewise, proposals for change are explored in an introductory manner. Why does it become essential to think about the university from a pluriversal, sociohistorical and gender perspective, depatriarchal and intercolonial perspective?